2014
DOI: 10.1186/1750-1172-9-5
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Erythrocyte Infusion of Dexamethasone Reduces Neurological Symptoms in Ataxia Teleangiectasia Patients: Results of a Phase 2 Trial

Abstract: BackgroundAtaxia Teleangiectasia [AT] is a rare neurodegenerative disease characterized by early onset ataxia, oculocutaneous teleangiectasias, immunodeficiency, recurrent infections, radiosensitivity and proneness to cancer. No therapies are available for this devastating disease. Recent observational studies in few patients showed beneficial effects of short term treatment with betamethasone. To avoid the characteristic side effects of long-term administration of steroids we developed a method for encapsulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 27 publications
1
95
0
Order By: Relevance
“…51 There is currently no treatment available for AT other than palliative care. Interestingly, Chessa et al 52 found that treatment with the antiinflammatory steroid betamethasone improved neurological symptoms for AT patients, though it remains to be seen whether this effect was mediated by the immunosuppressive properties of the drug. Our work further strengthens the argument that targeting inflammation may be a promising clinical intervention for some of the symptoms of this devastating disease.…”
Section: Discussionmentioning
confidence: 99%
“…51 There is currently no treatment available for AT other than palliative care. Interestingly, Chessa et al 52 found that treatment with the antiinflammatory steroid betamethasone improved neurological symptoms for AT patients, though it remains to be seen whether this effect was mediated by the immunosuppressive properties of the drug. Our work further strengthens the argument that targeting inflammation may be a promising clinical intervention for some of the symptoms of this devastating disease.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis is important to help ensure affected children and their families receive appropriate support with proper multidisciplinary management and the opportunity to have genetic counselling support if they would like 8. Earlier diagnosis will ensure affected children can be offered tailored support from experienced professionals, via referral to the national centre, and also an opportunity to participate in research into potential therapeutic options 9. Finally, early diagnosis will lead to avoidance of radiation-based investigations, for example, high-resolution CT (HRCT) in a radiosensitive group with an increased risk of malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…The techniques by which RBC-based delivery systems would be collected and manufactured will likely depend on their application and source. As one example, the EryDex system for RBCs loaded with dexamethasone utilizes a simple 50 mL peripheral blood draw that is then loaded using a proprietary RBC loading device [202,203]. …”
Section: Current Challenges and Opportunitiesmentioning
confidence: 99%